Dinâmica das espacialidades rurais em territórios coloniais - Vidal, Lisane Regina (2008)
The work had as an objective to identify and characterize not only the family colonial system but also the dynamics that act upon the rural spatiality altering and integrating its production and reproduction relations determining a new system of production integrated to the market that is aggregated to the old colonial system. The methodological ways were structured through a systematic approach, a historicaldescriptive review and of critical analysis. The methodological procedures were constituted by techniques, data collection and auxiliary tools of investigation. The German immigrants’ reterritorialization in the far South of Brazil attended to strategic politics interests, both of settlement and supplement to the Brazilian Empire. In this way, Santo Ângelo colony received immigrants of Germanic culture who inserted in that space their ways of life, habits and culture, forming colonial territories. In the beginning of the colonization, the colonial activities were based on the social group survival, permitting the development of polycultivations that started to attend places, villages and cities that were being developed. In this way, the first forms of commercialization emerged in accordance with the colonial model, singular until now in Brazil. The external relations of these groups opened way to the entrance of new activities in the colonies that incorporate slowly new systems of production until the agriculture modernization phase. Then, the CAIs system and growth specialization were adopted resulting in the changing of agriculturists into modern familiar producers. However, an insignificant dimension of the available land besides its absence of capital guided to the production relations’ exhaustion due to the maximization of natural resources, marginalizing small rural establishments and provoking rural emigration. This situation of inertia in Agudo’s rural areas guided the familiar producers to aggregate new alternatives (familiar craftsmanship agroindustry) generators of incomes and caterings of Germanic cultures transported through their codes, due to their reterritorialization. Nowadays, these novelties make possible the social group’s permanence in the countryside keeping their colonial culture, but under a new production system integrated to the market.